Alfa-nauka na Uniwersytecie Lwowskim: historia, postacie, osiągnięcia (z okazji 110. rocznicy założenia Zakładu Muzykologii Uniwersytetu Lwowskiego) - Hrab, Ulana (Musica Galiciana. Kultura muzyczna Galicji w kontekście stosunków polsko-ukraińskich, 2025)
The history of musicology as a component of the history of humanitarian science from ancient times to the 20th century is considered. The meaning of the term „alpha science” in relation to musicology is revealed, which was introduced by the Dutch scientist Rance Bode, who claims that the musical laws created by musicologists acquire universal meaning and find their place in the field of other Humanities. In the 19th century, musicology became an independent university discipline with its own methodology and research methods, which were established for centuries in musicological practice. The principles of university education, which embody the Idea of the University, formulated and systematized in the works of German philosophers, are highlighted, and the place of musicology in the commonwealth of university disciplines is determined. The history of the Department of Musicology of the Lviv University, created in 1912–1939 by the Polish medievalist- musicologist and ethnographer Adolf Chybiński, is investigated, the signs of A. Chybiński „Lviv school of musicology”, the directions of scientific activity of his Polish and Ukrainian students and its influence on the post-war development of Ukrainian musicology are revealed.